PENERAPAN MODEL PEMBELAJARAN KOOPERATIF METODE QUESTION STUDENT HAVE UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 130 PEKANBARU - Hadi, Widya Yunilda; ', Lazim; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was carried out because the low Social Studies learning outcomes of students and many students who did not reach the KKM. From 35 students, only 13 students who achieve KKM while students who did not reach the KKM as much as 22 people. The purpose of this research is to improve the results of the study of grade IV SD Negeri 130 Pekanbaru with the implementation of the model of cooperative learning methods question student have. The research results obtained the percentage of the activity of the teacher of the first meeting I on cycle of 62,50%, at the meeting of the two rose to 75%. At cycle II the first meeting, activities teachers rose to 83,30% and at the meeting of the two become 87,50% with good category. The percentage of the activity the students at cycle I the first meeting of 54,17% rose to 65,50% on the second meeting. Later in the cycle II of the first meeting of the students rose to 79,17% and have increased again on the second meeting of 91,67% with very good category. The results of student learning in classical increase seen from the basic score, the cycle I and II namely 37.16 percent rose to 61,29% and rose again become 82,35%. For the improvement of the results of the Social Studies learning students also increased by 17,69% at cycle I and rose again by 26,88% at cycle II. It can thus be understood that the implementation of the model of cooperative learning methods question student have can improve the results of learning social studies grade IV SD Negeri 130 Pekanbaru.Keywords: cooperative learning, question student have, learning result of social studies